Pemeriksaan Kesehatan Lansia di Posyandu Lansia Dusun Demangan Gunungan, Pleret, Bantul - Widiany, Fery Lusviana (Universitas Respati Yogyakarta, 2019)
In Indonesia, there has been an increase in the percentage of elderly groups compared to other age groups which have been quite rapid since 2013. As a result of population projection of 2010-2035, Indonesia will enter the aging period, whereas 10% of the population will be 60 years or older. With increasing age, physiological functions decline due to the aging process so that non-communicable diseases appear in the elderly. In Demangan Gunungan hamlet, Pleret, Bantul, elderly integrated service post activities were carried out in the form of weight measurements, blood pressure checks, and elderly gymnastics. However, there has never been a gout examination in the elderly because of limited access to health services, limited costs, and lack of information regarding the importance of routine laboratory examinations. So it is necessary to do community service activities in the form of uric acid examination and nutrition counseling to the elderly in the hamlet. Community engagement activities carried out in Demangan Gunungan hamlet, Pleret, Bantul in the form of uric acid examination in the elderly and providing nutrition counseling related to a good diet in anticipating and overcoming health problems, especially gout (hyperuricemia). The activity was attended by 40 people, consisting of 34 elderly people and 6 cadres. The results of uric acid examination showed that there were more elderly people in Demangan Gunungan hamlet, Pleret, Bantul (55%) than those who did not experience hyperuricemia (45%). This community engagement activities achieved results according to the target based on the attendance of participants and program evaluation. It was expected that there would be a decrease in the number of elderly health problems and a decrease in the number of gout sufferers (hyperuricemia) in Demangan Gunungan, Pleret, Bantul.Keywords: elderly, health check, gout (hyperuricemia), nutrition counseling, elderly integrated service post.